The Judge in the Islamic Balance - Al-Saadi, Arwa Ahmed Hamood; Hafshah, Hafshah; Mostafa, Mostafa; Mursyidi, Mursyidi; Albab, Moh. Ulul (Syura: Journal of Law, 2023)
This academic paper delves into the intricate and multifaceted role of the judge within the context of Islamic jurisprudence. Drawing from the rich and diverse heritage of Islamic legal traditions, the study seeks to illuminate the judge's pivotal position as the embodiment of justice, ethics, and social equilibrium in Muslim-majority societies. It explores the historical evolution of Islamic jurisprudence and its relevance in contemporary legal systems, emphasizing the judge's duty to uphold Islamic law while adapting to the changing demands of modern society. In conclusion, this paper provides a comprehensive analysis of the judge's pivotal role in the Islamic legal system and its relevance in the modern world. It underscores the importance of preserving the integrity and independence of the judiciary while adapting to the evolving needs of Muslim-majority societies. Understanding the judge in the Islamic balance is essential for promoting justice, fostering social harmony, and maintaining the principles of Islamic jurisprudence in a contemporary global context.